2012
DOI: 10.4103/0019-5413.96368
|View full text |Cite
|
Sign up to set email alerts
|

Tumor like swellings arising from Hoffa’s fat pad: A report of three patients

Abstract: We report three rare cases of tumor-like conditions arising from Hoffa's fat pad (HFP). Patients were having persistent knee pain, the cause of which was not diagnosed by the general physician, and then were referred to us for knee pain. Magnetic resonance imaging revealed the lesions to be arising from HFP (ganglion cysts and hemangioma), as was suggested by clinical findings. Anatomy, pathology, and radiological features of the Hoffa's disease are described here to increase awareness in orthopedic community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Ghate et al 12 found a ganglion cyst in one patient, hemangioma in one patient and intraarticular cystic lesion in the medial region originating from IFP in another patient, as a result of post-surgical histopathological examinations in the Hoffa's syndrome case series.…”
Section: Singh Et Almentioning
confidence: 96%
“…Ghate et al 12 found a ganglion cyst in one patient, hemangioma in one patient and intraarticular cystic lesion in the medial region originating from IFP in another patient, as a result of post-surgical histopathological examinations in the Hoffa's syndrome case series.…”
Section: Singh Et Almentioning
confidence: 96%
“…This improvement is quoted as from "pain nearly resolved" in Kelly et al [22] to "resolution of symptoms/pain free" in nearly all the other papers. Ghate et al [32] reported two cases that involved open resection of IFP tumours which were asymptomatic at follow-up, but also showed improvement using the Cincinnati Knee Score. This was the only case report that demonstrated a quantitative improvement following the operation.…”
Section: Resolution Of Symptomsmentioning
confidence: 99%
“…None of the articles reported that the patients were unable to return to work or to their usual activities following the operation. In the case reports there was no quantitative measure of function, apart from the aforementioned Ghate et al [32] article reporting the Cincinnati Knee Score.…”
Section: Restoration Of Functionmentioning
confidence: 99%
“…I read with great interest the article by Ghate et al 1. The authors must be complimented for bringing out some rare pathology of the knee in the limelight.…”
mentioning
confidence: 99%
“…Though the precise function of the IFP is unknown, studies have shown that it may play a role in the biomechanics of the knee or act as a store for reparative cells after injury 1. It is intriguing to assume that HFP has some distinguished characteristics by which a variety of pathology like ganglionic cyst, hemangioma, villonodular synovitis, chondroma, etc., can develop from this fat pad, inside the knee joint.…”
mentioning
confidence: 99%